Fully Loaded Micromotors for Combinatorial Delivery and Autonomous Release of Cargoes. Issue 14 (6th April 2014) - Sattayasamitsathit, Sirilak; Kou, Huanhuan; Gao, Wei; Thavarajah, Walter; Kaufmann, Kevin; Zhang, Liangfang; Wang, Joseph
<x xml:space="preserve">Abstract</x> Integrating functional self‐propelled Zinc micromotors are created by coupling electrodeposition with hard dual‐templating synthesis. The micromotors concurrently possess four robust functions including a remarkably high loading capacity, combinatorial delivery of cargoes, autonomous release of encapsulated payloads, and self‐destruction. This concept could be expanded to simultaneous encapsulation of various payloads for different functionalities such as therapy, diagnostics, and imaging. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>